IMPLIKASI PERUBAHAN UNDANG-UNDANG PEMERINTAHAN DAERAH TERHADAP KEWENAGAN TATA KELOLA PEMANFAATAN ENERGI DAN SUMBERDAYA MINERAL OLEH PEMERINTAHAN DAERAH DI INDONESIA - Rizky Setiawan (UIR Press, 2018)
This paper attempts to examine the authority of the Regional Government following the amendment of the Regional Government Law Number 32 of 2004 to Law No. 23 of 2014. The compilation of this paper is based on a review of Library and Legislation. One of the important points in the amendment of the Law on Regional Government relates to the authority of the Regional Government in the Management of Mineral Resources. The implications of the amendments to the Law on Regional Government include the decreasing authority of the Government of Tinggua II related to the granting of permits and supervision of the utilization of energy and natural resources in the area of regencies / cities in Indonesia. public policy making (public policy making). Energy and Mineral Resources have now played a very important role in the development of the Indonesian economy, which serves as one of the backbone of state revenue. The management of Natural Resources needs to be done optimally, efficiently, transparently, sustainably and environmentally sound, and equitable in order to gain the greatest benefit for the people's sustainable prosperity.